2022
DOI: 10.1080/01634372.2021.2019163
|View full text |Cite
|
Sign up to set email alerts
|

Are Older People Living Alone Socially Isolated? A Qualitative Study of Their Experiences

Abstract: This article discusses the experiences of social isolation among older people living alone. The current state of knowledge suggests that they are at a higher risk of social isolation which, in turn, can compromise their health and well-being to varying degrees. Yet, few qualitative studies have tried to understand the subjective experience of living alone and the ways it can impact older people's relationships. The data presented here are based on 43 individual interviews with men and women aged 65 to 93 livin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…However, patients being alone are not necessarily all living alone 35 , but living alone can reflect the degree of being alone to a certain extent. A qualitative study found that living alone means being alone for some elderly individuals 36 . Hence, there may be an overlap between the state of living alone and being alone, and this relationship may vary among different people.…”
Section: Discussionmentioning
confidence: 99%
“…However, patients being alone are not necessarily all living alone 35 , but living alone can reflect the degree of being alone to a certain extent. A qualitative study found that living alone means being alone for some elderly individuals 36 . Hence, there may be an overlap between the state of living alone and being alone, and this relationship may vary among different people.…”
Section: Discussionmentioning
confidence: 99%
“…49 For some, living alone is not seen as a problem as they are resilient and maintain satisfactory social relations with family and peers, while for others living alone is more problematic. 50 Individual variation in coping strategies for living alone through the pandemic could explain our small OR.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, the elderly’s personalities also contributed to their social isolation ( 31 , 39 , 40 ): they either prefer being alone ( 41 ) or display a reluctance to seek help from family, friends, and neighbors, for fear that they would be viewed as a burden to others ( 36 ). This not only exists in Western societies but also in Chinese society where the elderly in social isolation displays a sense of self-reliance for fear that they would bother other people ( 27 , 30 ).…”
Section: Literature Reviewmentioning
confidence: 99%